Dead weight: an analysis of how obesity is dealt with in Brazilian legislation - Olivo, Ana Maria; Figueiredo, Débora de Carvalho (Language and Law / Linguagem e Direito, 2019)
The objective of this study is to analyze Brazilian laws regarding overweight and obesity in order to understand how these two concepts, and the relation between weight and health, are construed through discourse. In order to do that, we rely on the ‘Legitimation in Discourse’ framework proposed by van Leeuwen (2007). The results indicate that Brazilian legislation defines obesity basically on the basis of the BMI and focuses on obesity as a result of inadequate individual choices, which is a reductive interpretation of a complex social problem.